Enseñanza-aprendizaje de programación de computadoras: avances en la última década - Ibarra-Zapata, Ronald-Eduardo; Castillo-Cornelio, José-Orlando; Trujillo-Natividad, Pedro-Crisologo; García-Villegas, Christian; Yanac-Montesino, Rannoverng; Pando, Brian (Revista Científica, 2021)
In recent years, computer programming has become a highly demanded activity worldwide as part of software development. Training in this area is given from the basic levels of education. According to the reviewed publications, there are many basic and higher-level works involving techniques, methodologies, and tools to support the learning process. Despite this, it is necessary to continue with the contributions to the subject. The purpose of this work is to identify the artifacts proposed for the teaching-learning of computer programming through a systematic mapping of literature during the period 2010-2020. The results show the existence of efforts to propose and validate methodologies and strategies for teaching at the course level, leaving open research opportunities on evaluation guides, tools, and methods to accompany this process.